A CFD–CSD coupling method for simulating the dynamic impact and expulsion of fragile foreign objects from the 'inlet–bypass duct' junction of a turboprop aircraft. Issue 1 (31st December 2022) - Baigang, Mi
Abstract : Frequently appearing fragile hail, ice and other foreign objects pose great threats to advanced turboprop aircraft when they enter the intake system of the engine. However, it is difficult to simulate the effects of these objects as complicated aerodynamic and dynamic impact coupling phenomena are involved. Regarding a turboprop aircraft inlet with a bypass duct as the subject of the research reported in this article, a coupled Computational Fluid Dynamics–Computational Structural Dynamics (CFD–CSD) numerical simulation method is established based on an unstructured dynamic mesh and impact dynamics technology to solve the phenomena of 'motion–collision–fragmentation–fragment motion' for foreign objects such as fragile ice and hail entering the inlet. Based on airworthiness specifications, external hail and ice at the lip and inner lower wall of the inlet are modelled. Moreover, the dynamic motion of these foreign objects and their effects on the aerodynamic performance of the inlet system during the process are simulated and analysed in depth. The results show that high-speed hail breaks into small debris after collision, which may not cause a serious threat to the engine. In addition, the total pressure recovery coefficient and distortion rate are not heavily changed during the process. However, large pieces of ice at the lip of the inlet may lead to large-size fragments that impact the inner wall of the inlet, thus increasing the threat to the safety of the engine. Also, serious shielding and interference of large pieces debris with the inner flow in the dynamic process decrease the total pressure recovery coefficient while increasing the distortion rate, especially in the junction area between the inlet and the bypass duct. In particular, ice in the icing zone located in the inner lower part of the inlet should be of much more concern owing to the fact that ice in this region is more likely to fly directly into the main engine and cause a serious threat.